The wellbeing economy: Possibilities and limits in bringing sufficiency from the margins into the mainstream - Hayden, Anders; Dasilva, Clay (Frontiers in Sustainability, 2022)
The idea of sufficiency faces great obstacles in contemporary political economies in which production and consumption growth has long been considered imperative. Despite evidence supporting calls for a sufficiency-oriented, post-growth approach to environmental challenges, only pro-growth environmental perspectives have found significant mainstream political support until now. However, one recent formulation that has a strong affinity with a sufficiency approach – a wellbeing economy – has found growing support among mainstream political actors including governments and international organizations. Does the growing support for a wellbeing economy represent the long-sought breakthrough for a sufficiency-oriented, post-growth environmental approach? To help answer this question, we conduct case studies of New Zealand, Scotland, and Iceland – the three founders of the Wellbeing Economy Governments (WEGo). These nations have (to varying degrees) taken steps to downplay the centrality of economic growth and instead highlight wellbeing as the ultimate goal. They have also moved “beyond GDP” by introducing new wellbeing measurements and using them in policymaking. However, movement in a post-growth direction is limited by continuing dependence on economic growth to achieve intermediate goals, such as employment creation and provision of welfare state services, that are closely associated with the goal of wellbeing. We therefore characterize the emerging practice of the wellbeing economy as a “weak post-growth” approach. To become a “strong post-growth” perspective, it needs to be linked to a much more challenging project of disentangling contemporary societies’ dependence on economic growth. The article includes a discussion of ways that WEGo nations could contribute to addressing that considerable challenge and build on the sufficiency-oriented elements evident in the wellbeing economy.